Nursing Intervention Toward Quality of Life of Patients Undergoing Hemodialysis: A Systematic Review - Susanto, Gunawan; Upoyo, Arif Setyo (STIKep PPNI Jawa Barat, 2024)
Aims: Patients diagnosed with chronic renal disease commonly experience a diminished quality of life. This systematic review endeavors to discern nursing interventions aimed at enhancing the quality of life among individuals with chronic kidney disease undergoing hemodialysis. These interventions adopt a holistic approach, encompassing psychological, social, and physical aspects. Methods: A systematic review methodology was employed, utilizing ProQuest, Science Direct, and Google Scholar to search for relevant publications. In order to retrieve pertinent information, the databases were searched for complete English-language research articles published from 2013 to 2023. Results: This study investigates two intervention categories, specifically physical and non-physical, aimed at improving the quality of life for individuals undergoing hemodialysis due to chronic renal disease. Deliberations reveal that non-physical activities positively impact the psychological and social well-being of chronic kidney disease patients undergoing hemodialysis, whereas physical exercise promotes increased strength and endurance Conclusions: Dialysis has an adverse effect on all dimensions of Quality of Life for individuals with Chronic Kidney Disease. This review serves as a valuable resource for clinicians, offering insights into the implementation of comprehensive nursing interventions for Chronic Kidney Disease patients undergoing dialysis, encompassing physical, psychological, and social aspects. Subsequent research endeavors should prioritize exploring the spiritual dimension, given the promising outcomes observed in spiritual interventions, which have demonstrated effectiveness in mitigating pain, addressing concerns related to death, and enhancing overall well-being.